2001
DOI: 10.2165/00003088-200140110-00002
|View full text |Cite
|
Sign up to set email alerts
|

Individualising Aminoglycoside Dosage Regimens after Therapeutic Drug Monitoring

Abstract: Measurements of aminoglycoside concentration in serum are used to individualise dosage regimens (dose per administration and/or administration interval) with the goal of attaining the desired therapeutic range as quickly as possible. Therapeutic range is defined in terms of peak concentration (to monitor effectiveness) and trough concentration (to avoid toxicity). This article focuses on methods to individualise aminoglycoside dosage regimens in the context of extended dosage intervals. Simple pharmacokinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Unlike nonBayesian methods (eg, nomogram, non-Bayesian least-squares method), the maximum a posteriori estimation displays better predictive performance for individualized drug dosage, because it incorporates some prior information (ie, covariates, PK model, residual error model, prior distributions). 16,17 In addition, the Bayesian estimation can be performed using a limited number of concentrations, as is usually the case in ICU patients. However, such a method depends on the quality of the population estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike nonBayesian methods (eg, nomogram, non-Bayesian least-squares method), the maximum a posteriori estimation displays better predictive performance for individualized drug dosage, because it incorporates some prior information (ie, covariates, PK model, residual error model, prior distributions). 16,17 In addition, the Bayesian estimation can be performed using a limited number of concentrations, as is usually the case in ICU patients. However, such a method depends on the quality of the population estimates.…”
Section: Introductionmentioning
confidence: 99%
“…A number of approaches have been advocated including trough or predose plasma concentrations of < 0.5 or <1 or < 2 mg/L, area under the plasma concentration-time curve (AUC) and various nomograms utilising population based/ Bayesian pharmacokinetics [4][5][6][7]. A recent consensus document from the United Kingdom Cystic Fibrosis Trust recommended that a trough level of tobramycin of < 1 mg/L should be adopted for drug monitoring as used in the TOPIC study [3].…”
Section: Introductionmentioning
confidence: 99%
“…Many pharmacokinetic (PK) studies have reported a positive correlation between aminoglycoside serum clearance or elimination rate constant and estimated or measured creatinine clearance (CL CR ) (22,23,34,41). Modelbased, Bayesian estimation is considered to be the most efficient method to monitor and adjust dosage regimens of aminoglycosides in patients (2,36). Such a procedure requires the prior identification and validation of the best structural and covariate models in a patient population (21).…”
mentioning
confidence: 99%